Segregation formation, thermal and electronic properties of ternary cubic CdZnTe clusters: MD simulations and DFT calculations - Kurban, M.; Erkoç Ş. (Elsevier B.V., 2017)
Surface and core formation, thermal and electronic properties of ternary cubic CdZnTe clusters are investigated by using classical molecular dynamics (MD) simulations and density functional theory (DFT) calculations. In this work, MD simulations of the CdZnTe clusters are performed by means of LAMMPS by using bond order potential (BOP). MD simulations are carried out at different temperatures to study the segregation phenomena of Cd, Zn and Te atoms, and deviation of clusters and heat capacity. After that, using optimized geometries obtained, excess charge on atoms, dipole moments, highest occupied molecular orbitals, lowest unoccupied molecular orbitals, HOMO-LUMO gaps (Eg), total energies, spin density and the density of states (DOS) have been calculated with DFT. Simulation results such as heat capacity and segregation formation are compared with experimental bulk and theoretical results. © 2017 Elsevier B.V.
Keywords: Electronic structure; Molecular dynamics; Order parameter; Specific heat